Movie Genre Classification from RGB Movie Poster Image Using Deep Feed-forward Network - Mushtaque Ahmed Korai; Altaf Hussain Bouk; Abdul Hameed Sindhi (Yanbu Journal of Engineering and Science)
A movie poster image is one of the important media in the filmmaking process, providing valuable information about the movie, such as movie titles, characters, and genres. Identifying a movie genre from a poster can be a daunting task, as it can relate to multiple genres. To solve this problem, this paper uses a deep feedforward neural network to classify movie genres from movie poster images. In this regard, we used and trained a state-of-the-art InceptionV3 deep neural network. The network is trained on our dataset consisting of 36,423 movie poster images taken from the IMDB website, which is categorized into 28 genres. The model predicts the top three classes with the highest probability of a particular movie poster.